Apricots Before the Sky. - Marasli, Elçin. (Tufts University. Tisch Library., 2016)
Apricots Before the Sky was inspired by my first visit to the Empire State Bulding in NYC. On top of the building, a friend told me she has never eaten apricots before. Coming from Turkey, where apricots are consumed year-round, I was inspired to write a personal story about fear of skyscrapers. Illustrated by the photos I took, presented with a cover image of a close-up of an apricot's skin, Apricots Before the Sky explores the clash between the industrial and the organic. Across a hundred pages of various combinations of black and white imagery and orange printed typography, the book performs a rhythmic travel through various time periods and polar destinations that ultimately form the unified base of a personal psychological experiment. The relationship between visual image and literary text are essential to my art making process. I challenge myself in terms of critical thinking, and integrate symbolism into my body of work which reads through images and sees through words. I refuse to work in any specific medium, as I consider the very core of my work to be an analytical appraisal of the various forms of creating artistic content and meaning. My medium is the aesthetic inquiry itself. With a growing interest in the semiotic combination of image and word, I seek to understand the interchangeable use of different media and degrees of communication in the fine arts.